Multifunctional silver coated E-33/iron oxide water filters: Inhibition of biofilm growth and arsenic removal - Nadagouda, Mallikarjuna N.; Bennett-Stamper, Christina; White, Colin; Lytle, Darren (RSC advances, 2012)
Bayoxide® E33 (E-33) is a widely used commercial material for arsenic adsorption composed of a mixture of iron oxyhydroxide and oxides. Primarily used to remove arsenic from water, it is a non-magnetic, iron oxyhydroxide/oxide used in fixed bed pressure filters that generally lack multi-functionality. Like other adsorptive media, it is subject to surface fouling by precipitates, including iron and manganese, and biofilms that can create diffusion limitations. Modifying the surface of E-33 with silver nanoparticles to enhance the material properties could add multi-functionality and be beneficial, providing that the original arsenic adsorption properties are not compromised. Commercially available arsenic adsorption media (E-33) was combined to create core-shell composites, i.e. silver coated goethite (in magnetic and non magnetic forms), that is capable of removing arsenic, acting as an antibacterial, and has magnetic properties. Several green approaches were developed to prepare the silver coated goethite and it was tested for arsenic removal and antibacterial activity. Samples were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray florescence spectroscopy (XRF), and inductively coupled plasma mass spectroscopy (ICP-MS).